Buckwheat Hull-Enriched Pasta: Physicochemical and Sensory Properties - Katarzyna Sujka; Grażyna Cacak-Pietrzak; Alicja Sułek; Karolina Murgrabia; Dariusz Dziki (Molecules, 2022)
This work aimed to evaluate the effect of partial replacement of semolina with 0, 1, 5, 10, 15, and 20% of ground buckwheat hull (BH) on the chemical composition, antioxidant properties, color, cooking characteristics, and sensory properties of wheat pasta. Pasta samples were prepared by dough lamination (tagliatelle shape) and dried at 55 °C until the moisture content was 11–12% (wet basis). Analyses of samples showed that the addition of BH caused an increase in fiber content in pasta from 4.31% (control pasta) to 14.15% (pasta with 20% of BH). Moreover, the brightness and yellowness of BH-enriched products were significantly decreased compared to the control sample, and the total color difference ranged from 23.84 (pasta with 1% of BH) to 32.56 (pasta with 15% BH). In addition, a decrease in optimal cooking time, as well as an increased weight index and cooking loss, was observed in BH-enriched pasta samples. Furthermore, BH-enriched cooked pasta had significantly higher total phenolic content and antioxidant activity but an unpleasant smell and taste, especially if the level of BH was higher than 10%.